Pemanfaatan Tanaman Herbal Sebagai Obat Tradisional Untuk Kesehatan Masyarakat Di Jempong Timur, Kecamatan Sekarbela, Kota Mataram - Nurvazila Virdaus; Tina Warasari; Laela Najmi; Anis Syakiratur Rizki; Husnul Budiatman Dani; Firman Ali Rahman (Aksi: Jurnal Pengabdian Masyarakat, 2024)
Herbal drinks are an alternative treatment method that is increasingly popular with the public, especially as a solution to improve health and endurance. This research aims to explore the use of medicinal plants such as ginger, turmeric and cinnamon to make herbal drinks that can increase the body's immunity. The method used is community service, with production stages including preparing ingredients, boiling, and community service.  Research results show that this herbal drink is not only rich in beneficial active compounds, but also has the potential to treat various health conditions, including digestive disorders and inflammation. Discussions revealed that although there are challenges in public acceptance, especially among the younger generation, innovations in packaging and presentation can increase their interest in plant-based beverage products. In conclusion, herbal drinks have great potential as safe and effective alternative medicines and can preserve the use of traditional spices in Indonesia.